Bercerita sebagai Metode Mengajar bagi Guru Raudlatul Athfal dalam Mengembangkan Kemampuan Dasar Bahasa Anak Usia Dini di Desa Ngembalrejo Bae, Kudus (PIAUD IAIN Kudus, 2015)
One of the methods applied by early childhood educators is storytelling.Storytelling is helpful for them. However, practically, not all them is capable ofcarrying out this method. The challenge is the limited media that accompanies theapplication of this method. Storytelling is very attractive to the world of children,especially in early childhood education, but are less socialized to give benefits forthe early childhood educators, especially those that live in some district. While thereason is similar to the limitations of the media